Efektivitas Peran Auditor Internal di UIN Syarif Hidayatullah Jakarta yang Ditunjukkan Oleh PP No. 60 Tahun 2008: “Sistem Pengendalian Intern Pemerintah (SPIP)” - Yusar Sagara (Esensi: Jurnal Bisnis dan Manajemen, 2015)
The effectiveness of the Internal Auditor's role in UIN Syarif Hidayatullah Jakarta Shown By Regulation No. 60 of 2008: "Government Internal Control System (SPIP)". This study aims to determine the factors that can create conditions for a good university governance focus more factors that analyzed the role of internal auditors in UIN Syarif Hidayatullah Jakarta. This research was conducted with descriptive method, using research data sources such as government regulation, Regulation, Regulation of the Inspector General, the Statute of UIN Syarif Hidayatullah Jakarta and Regulations Rector. Data collected later dideskriptifkan, analyzed logically, systematic, and consistent with the research paper more detailed and in-depth. Therefore in view of the explanatory data, this research study is referred to as the analytical descriptive. The main finding of this study is that the regulations governing the Internal Control Unit (SPI), especially concerning the role, functions, duties, powers and responsibilities and organizational support is adequate. The findings of the examiner's next is the terminology used by SPI at UIN Syarif Hidayatullah Jakarta is right. Competence of personnel seen backdrop of education is appropriate. Limitations of this study is factor analyzed only on the role of auditors. The author suggests the existence of such advanced research is to expand the knowledge management factors.DOI: 10.15408/ess.v5i1.2336